2017
DOI: 10.3748/wjg.v23.i14.2505
|View full text |Cite
|
Sign up to set email alerts
|

New progress in roles of nitric oxide during hepatic ischemia reperfusion injury

Abstract: Hepatic ischemia reperfusion injury (HIRI) is a clinical condition which may lead to cellular injury and organ dysfunction. The role of nitric oxide (NO) in HIRI is complicated and inconclusive. NO produced by endothelial nitric oxide synthase (eNOS) activation plays a protective role during early HIRI. But eNOS overexpression and the resulting excessive NO bioavailability can aggravate liver injury. NO induced by inducible nitric oxide synthase (iNOS) may have either a protective or a deleterious effect durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 32 publications
2
23
0
3
Order By: Relevance
“…High iron contents and NO production in activated macrophages may lead to formation of electron paramagnetic resonance (EPR)‐detectable dinitrosyl iron complexes (DNICs) . On the other hand, NO microcirculation and elevated levels of NO were observed in liver injury, the condition of the high iron demand due to the enhanced cell proliferation, and were found beneficial for improved allograft function after transplantation . High Fe and LDL contents coincide also in normal hepatocytes due to the fundamental functions of liver, which are lipid metabolism and iron storage .…”
Section: Introductionmentioning
confidence: 99%
“…High iron contents and NO production in activated macrophages may lead to formation of electron paramagnetic resonance (EPR)‐detectable dinitrosyl iron complexes (DNICs) . On the other hand, NO microcirculation and elevated levels of NO were observed in liver injury, the condition of the high iron demand due to the enhanced cell proliferation, and were found beneficial for improved allograft function after transplantation . High Fe and LDL contents coincide also in normal hepatocytes due to the fundamental functions of liver, which are lipid metabolism and iron storage .…”
Section: Introductionmentioning
confidence: 99%
“…To date, only few studies have advocated independently the protective role on the hepatocyte of either preconditioning (30) or postconditioning (26,27) in both animal models and humans (39); however none has compared directly the effect of pre-to postconditioning. Furthermore, recent studies have concluded that during I/R injury there is over expression of iNOS and/or eNOS and their inhibition protects from I/R injury (40), therefore pointing towards a fine balance between beneficial and detrimental effects of the bioavailability of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Under different pathological conditions, hepatic I/R injury can be classified into warm and cold I/R injury according to the environmental temperature [115]. It is well known that hepatic I/R injury involves several mechanisms, including pH imbalance, calcium overload, mitochondrial dysfunction, ROS overproduction, anaerobic metabolism, activation of Kupffer cells and neutrophils, and the production of cytokines and chemokines [113, 114, 116, 117]. Despite significant improvements in surgical techniques and perioperative care, therapies to suppress hepatic I/R injury at the bedside remain limited largely due to the complex mechanisms [118].…”
Section: H2s In Hepatic Injurymentioning
confidence: 99%